The GCC Monetary Union : Some Considerations for the Exchange Rate Regime - Guerami, Behrouz (IMF Working Papers; Working Paper, 2003)
We compare the dollar peg to a dollar-euro basket peg as alternative exchange rate regimes for the incipient Gulf Cooperation Council (GCC) currency union. Quantitative evidence suggests basket peg does not dominate dollar peg for improving external stability. However, as GCC exports and external financial assets become more diversified, a more flexible exchange policy may be necessary for competitiveness and stability. Pegging the prospective common GCC currency to a basket, like the dollar-euro basket, may provide a conservative transitional strategy toward a more flexible exchange rate policy.